Hybrid density functional calculations of hyperfine coupling tensor for hole-type defects in MgAl2O4 - Platonenko, Alexander; Gryaznov, Denis; Kotomin, Eugene A.; Lushchik, Aleksandr; Seeman, Viktor; Popov, Anatoli I. (Elsevier B.V., 2020)
We have performed the density functional calculations (DFT) on the hole-type defects (V-centres) in magnesium aluminate spinel (MgAl2O4) following the results of recent paramagnetic resonance measurements (EPR) in Nucl. Inst. Methods Phys. Res. B 435 (2018) 31–37. The hybrid B3LYP functional calculations using large supercells of 448 atoms have demonstrated excellent results not only for bulk properties but also properties of the V-centres in MgAl2O4. Three types of V-centres have been considered and confirmed, namely V1, V2 and V22. The DFT calculations have revealed the atomic relaxation pattern and spin density distribution around the hole-type defects that is suggested as an important complement to the experiments. Moreover, the calculated hyperfine coupling constants (HCCs) have been analyzed and compared with those from the measured EPR spectra. A good agreement between the calculated and measured HCC values is observed and discussed.
This work has been performed within the framework of the EUROfusion Enabling Research project: ENR-MFE19.ISSP-UL-02 “Advanced experimental and theoretical analysis of defect evolution and structural disordering in optical and dielectric materials for fusion application”. The views and opinions expressed herein do not necessarily reflect those of the European Commission.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; MgAl2O4 (spinel); Hole-type defects (V-centres); Hybrid DFT calculations (B3LYP)